Conjunctival Metastasis as an Initial Sign of Small Cell Lung Cancer - Afsun Sahin; Nilgun Yildirim; Deniz Goren Sahin; Hikmet Basmak; Mustafa Acikalin (Case Reports in Medicine)
Introduction. To report a case of a conjunctival metastasis as the initial manifestation of small cell lung cancer. Methods. Observational case report. Results. A 50-year-old man without known systemic disease developed a conjunctival mass in his right eye. He underwent incisional biopsy of the tumor and systemic evaluation. Histopathologically, the conjunctival mass was a metastatic small cell carcinoma. Further evaluation revealed a primary small cell lung carcinoma with metastasis to liver and bones. The primary and metastatic tumors were treated with chemotherapy. Conclusion. Conjunctival metastasis may be the initial manifestation of lung cancer. It should be considered in the differential diagnosis of a deep conjunctival mass.